Enrichment strategy to enhance screening for novel cellulose-degrading enzymes from Malaysian palm oil mill effluent by constructing functional DNA metagenomic libraries - Ibrahim Ali , Noorbatcha; Hamzah, Mohd. Salleh (2015)
Functional metagenomic approach has proven to be powerful tool for identifying novel biocatalysts through high-throughput screening of DNA metagenomic library. Culture enrichment strategies are additional pre-screening methods to provide an attractive means of enhancing the screening hit rate. In this work metagenomic DNA library was made from Malaysian palm oil mill effluent (POME) microorganisms after culture enrichment experiment basing on natural selection principle. POME microorganisms were inoculated in a medium with similar chemical composition of POME and under controlled conditions of temperature, light, pH with the presence of carboxylmethylcellulose (CMC) for 10 days in order to allow growth of particular microorganisms with cellulose-degrading activities. Metagenomic DNA was extracted from both enriched and non-enriched cultures, 40kb sequences were end-repaired and migrated through 20cm agarose gel electrophoresis showing enhanced DNA concentration of enriched culture compared to the non-enriched culture. These DNA sequences were cloned to PCC1FOS fosmid, packaged in lambda phage and transformed into EPI300T1R. Titer test has shown that the cloning resulted in a high number of colonies from enriched cultures compared to normal metagenomic library. Further high throughput screening is being carried out to test the efficiency of enrichment strategy by comparing positive clones’ frequency between enriched and non-enriched libraries.